Rethinking Multipliers in a Globalized World - Nallari, Raj; Mba, Leopold Engozogo (2012)
This paper uses the central tool of an investment-savings and monetary-policy model with an augmented Philips curve and presents a few extensions of that model to analyze the multiplier effects of macroeconomic policies in the United States. In doing so, the authors incorporate realistic assumptions in the model related to the recent financial characteristics of the global economy. The monetary policy reaction function embeds a new augmented Taylor-rule incorporating housing and stock prices and the credit lending rate. And the household consumption and firm investment decisions incorporate housing and stock assets and the credit market frictions. The equilibrium income is derived and compared with the actual nominal gross domestic product of the United States for the period 1990 to 2009. More importantly, fiscal and trade multipliers are derived and discussed. The main finding is that government spending, tax cut, and trade multipliers are relatively smaller in size when more realistic features are incorporated in the model. The model simulation shows that the model can track actual gross domestic product reasonably well. The model should be further improved before it could be used for policy exercises.